MicroRNAs in Extracellular Vesicles in Sweat Change in Response to Endurance Exercise - Karvinen, Sira; Sievänen, Tero; Karppinen, Jari E.; Hautasaari, Pekka; Bart, Geneviève; Samoylenko, Anatoliy; Vainio, Seppo J.; Ahtiainen, Juha P.; Laakkonen, Eija K.; Kujala, Urho M. (Frontiers in Physiology, 2020)
Background: To date, microRNAs (miRs) carried in extracellular vesicles (EVs) in response to exercise have been studied in blood but not in non-invasively collectable body fluids. In the present study, we examined whether six exercise-responsive miRs -21, -26, -126, -146, -221 and -222 respond to acute endurance exercise stimuli of different intensities in sweat. Methods: We investigated the response of miRs isolated from sweat and serum EVs to three endurance exercise protocols: 1) maximal aerobic capacity (VO2max), 2) anaerobic threshold (AnaT) and 3) aerobic threshold (AerT) tests.. Sauna bathing was used as a control test to induce sweating through increased body temperature in the absence of exercise. All protocols were performed by the same subjects (n=8, 3 males and 5 females). The occurrence of different miR carriers in sweat and serum was investigated via EV markers (CD9, CD63 and TSG101), miR-carrier protein (AGO2) and HDL-particle marker (APOA1) with Western blot. Correlations between miRs in sweat and serum (post-sample) were examined. Results: Of the studied miR carrier markers, sweat EV fractions expressed CD63 and very weakly APOA1, while serum EV fraction expressed all the studied markers. In sweat EVs, miR-21 level increased after AerT and miR-26 after all of the endurance exercise tests compared with the Sauna (p<0.050). miR-146 after AnaT correlated between sweat and serum EV samples (r=0.881, p=0.004). Conclusion: Our preliminary study is the first to show that in addition to serum, sweat EVs carry miRs. Interestingly, we observed that miRs -21 and-26 in sweat EVs respond to endurance exercise of different intensities. Our data further confirmed that miR responses to endurance exercise in sweat and serum were triggered by exercise, and not by increased body temperature. Our results highlight that sweat possesses a unique miR carrier content that should be taken into account when planning analyses from sweat as a substitute for serum.